Microneedle electrode, wearable device and electronic device
By using composite silk protein material as the contact part of the microneedle electrode, the quantum tunneling effect of metal nanowires can be used to achieve the improvement of conductivity and biocompatibility, which solves the high contact impedance and wear of existing microneedle electrodes during skin contact. The discomfort problem achieves the effect of high sensitivity and long-term stable wear.
Patent Information
- Application Number
- CN202311010747.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-11
- Publication Date
- 2025-02-18
AI Technical Summary
The existing microneedle electrodes have a large contact impedance when in contact with the skin, have low wearing comfort, poor biocompatibility and breathability, which can easily cause skin allergies and damage.
Using composite silk protein materials including polymers, silk proteins and metal nanowires as the contact part of the microneedle electrode, the "quantum tunneling effect" of metal nanowires achieves highly uniform conductivity, and is both biocompatible and breathable. sex.
The microneedle electrode has the advantages of low contact impedance, high sensitivity, tight fit, flexible and skin-friendly, stable and durable, and can be worn for a long time, improving the wearing comfort and stability of electrical performance.
Smart Images

Figure CN119454039A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of medical devices, and in particular to microneedle electrodes, wearable devices and electronic devices. Background Art
[0002] With the development of economy, society and medical technology, people have paid more and more attention to their health. Modern medicine has long confirmed that various human physiological electrical signals, including electrocardiogram signals and electromyography signals, are important indicators of human health.
[0003] Physiological electrical signals are one of the most basic physiological phenomena of organisms. Common physiological electrical signals that can be monitored mainly include electromyography (EMG), electrocardiography (ECG), electroencephalography (EEG), electrodermal conductivity (EDA), electrooculography (EOG), electrogastric conductivity (EGG) signals, etc. Physiological electrodes are used to measure the above various physiological electrical signals of the human body. This kind of physiological electrical electrode actually converts the ion potential generated by electrochemical activities in the organism into a current that can be identified and characterized by the measurement system, acting as a transducer, and is essentially a type of sensor. Specifically, the current is conducted by ions in the organism, by electrons in electrodes and wires, and at the contact interface between the electrode and the human skin, the ion current is converted into an electron current, so that the organism and the measuring instrument system together form a current loop.
[0004] Therefore, the research, preparation and improvement of bioelectric electrodes have important scientific significance and practical application value. According to the conductive materials of bioelectric electrodes, bioelectric electrodes can be mainly divided into hard electrodes and flexible electrodes, and can also be divided into dry electrodes and wet electrodes. The current mainstream bioelectric electrodes include but are not limited to metal electrodes, Ag / AgCl gel wet electrodes, microneedle electrodes and fabric electrodes.
[0005] Microneedle electrodes are an important physiological electrical electrode developed in recent years. However, in the current process of using microneedle electrodes to monitor human health, the contact impedance between microneedle electrodes and the skin is large, the comfort level is low when worn, and the biocompatibility and air permeability of microneedle electrodes with human skin are poor when worn for a long time, which can easily cause skin allergies and damage. Summary of the invention
[0006] The purpose of this application is to provide a microneedle electrode, a wearable device and an electronic device. The microneedle electrode has the advantages of low contact impedance, high sensitivity, close fit, flexible and skin-friendly, stable and durable, and can be worn comfortably for a long time.
[0007] In a first aspect, the present application provides a microneedle electrode, the microneedle electrode comprising:
[0008] A microneedle body, wherein the microneedle body comprises a contact portion for contacting the skin, wherein the contact portion is made of a composite silk protein material, wherein the composite silk protein material is formed by a polymer, a metal nanowire and a silk protein through mesoscopic hybridization; and
[0009] A flexible base layer is electrically connected to the microneedle body.
[0010] The microneedle electrode provided in the present application has a contact portion that contacts the skin made of a composite silk protein material including polymers, silk proteins and metal nanowires. This composite silk protein material utilizes the microscopic directional reconstruction of metal nanowires, polymers and silk proteins, and achieves highly uniform conductivity on the surface and inside of the contact portion through the "quantum tunneling effect" of the metal nanowires. It also has biocompatibility and breathability, which enables the microneedle electrode to have excellent mechanical stability and chemical stability.
[0011] In some embodiments, the contact portion is a plurality of electrode needles arranged in an array. The electrode needles may be directly connected to the flexible base layer or indirectly connected thereto, which is not limited here.
[0012] In some embodiments, the end of the electrode needle has an arc surface. The present application has rounded the end structure of the electrode needle. Compared with other pointed cones, needle-shaped structures, etc., when the microneedle structure contacts the skin, it is not easy to remain partially in the skin. The microneedle electrode of the present application does not have a needle tip that pierces the skin. The electrode needle will not break after thousands of frictions, and the conductivity is not affected, so it can be used repeatedly.
[0013] In some embodiments, the electrode needle includes a cylindrical body and a hemispherical end. This structure has a better touch with the skin and can enhance wearing comfort.
[0014] In some embodiments, the diameter of the electrode needle is 400 μm to 600 μm; specifically, it can be 400 μm, 420 μm, 450 μm, 470 μm, 500 μm, 520 μm, 550 μm, 570 μm, 580 μm or 600 μm, etc., or other values within the above range, which are not limited here. From the perspective of cost and structural strength, the diameter of the electrode needle is preferably 500 mm to 550 mm.
[0015] In some embodiments, the protruding height of the electrode needle is 400 μm to 850 μm; specifically, it can be 400 μm, 500 μm, 550 μm, 600 μm, 700 μm, 750 μm, 780 μm, 800 μm or 850 μm, etc., or other values within the above range, which are not limited here. Preferably, the protruding height of the electrode needle is 500 μm to 750 μm. Controlling the protruding height of the electrode needle can ensure that the electrode needle of the microneedle electrode can fully and stably contact with human skin.
[0016] In some embodiments, the spacing between two adjacent electrode needles is 800μm to 1200μm, specifically 800μm, 850μm, 900μm, 950μm, 1000μm, 1050μm, 1100μm, 1050μm or 1200μm, etc., or other values within the above range, which are not limited here. It can be understood that the spacing between electrode needles affects the distribution density of electrode needles in the microneedle electrode. Too high density increases the cost, and too low density reduces the effective contact with human skin, thereby affecting the detection accuracy of the electrode. Preferably, the spacing between two adjacent electrode needles is 900μm to 1000μm.
[0017] In some embodiments, the contact portion is a contact layer having convex points on the surface. It can be understood that these surface convex points can increase the contact stability with the skin and enhance the transmission of myoelectric signals.
[0018] In some embodiments, the contact portion is a contact layer with a smooth surface. It can be understood that the smooth contact layer can reduce the foreign body sensation when in contact with the skin, and the wearing comfort can be further improved.
[0019] In some embodiments, the microneedle body further comprises a substrate, and the contact portion is disposed on at least a portion of the surface of the substrate. When the contact portion is an electrode needle, a plurality of electrode needles are arranged in an array on the surface of the substrate. When the contact portion is a contact layer with a convex surface or a contact layer with a smooth surface, the contact layer can be stacked on the surface of the substrate.
[0020] In some embodiments, the microneedle body is made of a composite silk protein material, and the substrate and the contact portion are integrally formed, that is, the substrate and the contact portion are cast by the composite silk protein material, which can simplify the preparation process, improve the overall structural stability of the substrate and the contact portion, and also achieve more uniform conductivity.
[0021] In some embodiments, the substrate has a receiving cavity, a flexible filling layer is disposed in the receiving cavity, and the flexible base layer seals the receiving cavity of the substrate; the contact portion is disposed on a surface of the substrate away from the receiving cavity.
[0022] It can be understood that filling a flexible filling layer in the receiving cavity of the substrate can reduce the amount of composite silk protein material used and reduce costs. At the same time, using a flexible filling material with better softness can improve the wearing comfort of the microneedle electrode after the microneedle electrode is in contact with the skin.
[0023] In some embodiments, the substrate is a cap-shaped structure, the substrate includes a main body and a brim, the main body is provided with a receiving cavity, a flexible filling layer is provided in the receiving cavity, and the brim is sealed and connected to the flexible base layer. Filling the receiving cavity of the substrate with a flexible filling layer can reduce the amount of composite silk protein material used and reduce costs. At the same time, the use of a more flexible filling material can improve the wearing comfort of the microneedle electrode after the microneedle electrode is attached to the skin.
[0024] In some embodiments, the metal nanowires include at least one of gold nanowires, silver nanowires, copper nanowires and stainless steel nanowires. These metal nanowires have good electrical conductivity. In the composite silk protein material, the metal nanowires can still show good overall electrical conductivity when the density is low. Preferably, the metal nanowires are silver nanowires.
[0025] In some embodiments, the aspect ratio of the metal nanowire is less than 1000; specifically, it can be 999, 950, 900, 850, 800, 750, 700, 650, 600, 500, 400, 300, 200, etc., which are not limited here. In order to reduce the cost of materials, the present application can select metal nanowires with an aspect ratio of less than 600 to prepare composite silk protein materials.
[0026] In some embodiments, the diameter of the metal nanowire is 60 nm to 100 nm, specifically 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc., and may also be other values within the above range.
[0027] In some embodiments, the length of the metal nanowire is 5 μm to 60 μm, specifically 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm or 60 μm, etc., or other values within the above range, which are not limited here. When the length of the metal nanowire is short, it is necessary to increase the distribution density of the metal nanowire in the composite silk protein material. When the length of the metal nanowire is long, the distribution density of the metal nanowire in the composite silk protein material can be reduced, but the longer the metal nanowire, the higher the production cost. Considering the overall conductivity and cost, the length of the metal nanowire is preferably 20 μm to 50 μm.
[0028] In some embodiments, the silk protein is selected from at least one of mulberry silk, tussah silk, and castor silk.
[0029] In some embodiments, the molecular weight of the silk protein is 25 kDa to 130 kDa, specifically 25 kDa, 50 kDa, 70 kDa, 80 kDa, 90 kDa, 100 kDa, 110 kDa, 120 kDa or 130 kDa, etc., or other values within the above range, which are not limited here.
[0030] In some embodiments, the mass content of the metal nanowires in the composite silk protein material is 2% to 10%, specifically 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., or other values within the above range, which are not limited here.
[0031] In some embodiments, the β-folding content of the composite silk protein material is 44% to 49%, and the β-crystal content is 35% to 40%; and / or the size of the β-crystals in the composite silk protein material satisfies: La<2.5nm, Lb<4.0nm, Lc<10.1nm.
[0032] In some embodiments, the polymer in the composite silk protein material is selected from at least one of polyurethane, polyacrylamide, polyvinyl alcohol and cellulose.
[0033] In some embodiments, the polymer in the composite silk protein material is a polyurethane having a hard segment and a soft segment, and the mass ratio of the hard segment to the soft segment is greater than 3:1.
[0034] In some embodiments, the hard segment is polyisocyanate and the soft segment is polyethylene glycol.
[0035] In some embodiments, the material of the flexible substrate layer is the same as that of the microneedle body, that is, the material of the flexible substrate layer may also be a composite silk protein material.
[0036] In some embodiments, the flexible filling layer is made of a polymer, and the polymer is selected from at least one of polyurethane, silicone, polyacrylamide, and natural polymers.
[0037] In a second aspect, the present application provides a wearable device, wherein the wearable device comprises the microneedle electrode described in the first aspect.
[0038] In a third aspect, the present application provides an electronic device, comprising the microneedle electrode described in the first aspect.
[0039] Compared with the prior art, this application has at least the following beneficial effects:
[0040] The microneedle electrode provided in the present application has a contact portion that contacts the skin made of a composite silk protein material including polymers, silk proteins and metal nanowires. This composite silk protein material utilizes the microscopic directional reconstruction of metal nanowires, polymers and silk proteins, and achieves highly uniform conductivity on the surface and inside of the contact portion through the "quantum tunnel effect" of the metal nanowires. It also has biocompatibility and breathability, so that the microneedle electrode has excellent mechanical stability and chemical stability, and has the advantages of resistance to salt spray, sweat, alcohol, soap solution, and cleaning. BRIEF DESCRIPTION OF THE DRAWINGS
[0041] The present application is further described below in conjunction with the accompanying drawings and embodiments.
[0042] Figure 1a A schematic diagram of the structure of the microneedle electrode provided in this application;
[0043] Figure 1b Another schematic diagram of the structure of the microneedle electrode provided in this application;
[0044] Figure 1c A schematic diagram of another structure of the microneedle electrode provided in this application;
[0045] Figure 2a A three-dimensional structural rendering of the microneedle electrode provided in this application;
[0046] Figure 2b A three-dimensional decomposition structure effect diagram of the provided microneedle electrode;
[0047] Figure 3 Schematic diagram of the actual application scenario of the microneedle electrode provided in this application;
[0048] Figure 4 A curve diagram showing the change in conductivity of the microneedle electrode provided in the present application as a function of the amount of metal nanowires added;
[0049] Figure 5 Schematic diagram of the quantum tunneling mechanism of metal nanowires in the microneedle electrode provided in this application;
[0050] Figure 6a A comparison chart of the β-folding content in the composite silk protein material and silk protein provided in the present application;
[0051] Figure 6b A comparison chart of the content of β crystallites in the composite silk protein material and silk protein provided in the present application;
[0052] Figure 7a Schematic diagram of impedance test results of the microneedle electrode prepared in Example 1 of the present application;
[0053] Figure 7bA schematic diagram of the signal-to-noise ratio test results of the microneedle electrode prepared in the embodiment of the present application;
[0054] Figure 8a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in sweat;
[0055] Figure 8b This is a comparison diagram of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in sweat;
[0056] Figure 9a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in concentrated salt water;
[0057] Figure 9b This is a comparison diagram of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in concentrated salt water;
[0058] Fig.10a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in vegetable oil;
[0059] Fig.10b This is a comparison diagram of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in vegetable oil;
[0060] Fig.11 This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after wearing for 5 days;
[0061] Fig.12 This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after low-temperature storage;
[0062] Fig.13a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after the stretching test;
[0063] Fig.13b This is a comparison diagram of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after the stretching test;
[0064] Fig.14a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after the bending test;
[0065] Fig.14b This is a comparison diagram of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after the bending test;
[0066] Fig.15a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after the wear resistance test;
[0067] Fig.15b This is a comparison chart of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after the wear resistance test. DETAILED DESCRIPTION
[0068] In order to better understand the technical solution of the present application, the embodiments of the present application are described in detail below with reference to the accompanying drawings.
[0069] It should be clear that the described embodiments are only part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0070] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0071] It should be understood that the term "and / or" used in this article is only a description of the association relationship of associated objects, indicating that there can be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0072] With the development of economic society and medical technology, people have paid more and more attention to their physical health. Modern medicine has long confirmed that various physiological electrical signals of the human body, including electrocardiogram signals and electromyography signals, are important indicators of human health. Therefore, the research, preparation and improvement of physiological electrical electrodes have important scientific research significance and practical application value. According to the conductive materials of physiological electrical electrodes, bioelectric electrodes can be mainly divided into hard electrodes and flexible electrodes, and can also be divided into dry electrodes and wet electrodes. The current mainstream physiological electrical electrodes include but are not limited to metal electrodes, Ag / AgCl gel wet electrodes, fabric electrodes and microneedle electrodes.
[0073] Metal electrodes are typical hard electrodes and dry electrodes. The working principle of metal electrodes is to use the excellent conductivity of metals, especially precious metals (such as gold, silver, etc.) to characterize human physiological electrical signals. The structure and manufacturing process are relatively simple. It is a human physiological electrical electrode that was widely used in the early days. However, metal electrodes have the following significant disadvantages: 1. When the metal electrode is large in size, it often has a higher modulus and hardness, resulting in poor fit with the skin and can bring significant pressure and abrasion; 2. The surface of the metal electrode is usually smooth. In the absence of anti-slip treatment, it is not in close contact with the skin, and it is easy to fall off or slip during exercise, resulting in the inevitable introduction of large motion noise in the process of physiological electrical signal acquisition; 3. Microcurrent is prone to polarization when passing through the metal electrode; 4. Most metal electrodes have poor corrosion resistance and poor biocompatibility, and are not suitable for long-term wear.
[0074] Ag / AgCl gel wet electrode is a widely used human physiological electrode. There is a layer of conductive gel on the surface of Ag / AgCl electrode, and the electrode contacts the skin through the conductive gel. The advantage of Ag / AgCl gel wet electrode is that it is easy to manufacture and use, and it is cheap. The disadvantages of Ag / AgCl gel wet electrode include but are not limited to: 1. The conductive gel is prone to dehydration and drying during long-term use, resulting in changes in the conductive properties of the electrode; 2. The chemical stability of the conductive gel is poor, and its tolerance to solutions such as sweat, alcohol, saline, sebum (and human secretions) is poor; 3. The gel will adhere to the skin surface during the process of human skin secreting sweat, which not only brings an uncomfortable wearing experience, but also leads to a decrease in conductive performance; 4. The skin needs to be pre-treated before using the gel wet electrode (such as shaving hair, exfoliating, applying conductive gel, etc.), which is cumbersome.
[0075] Fabric electrodes are flexible dry electrodes made from conductive yarns through a weaving process. They are a relatively new type of electrode used to measure physiological electrical signals of the human body. At present, the contact impedance between flexible fabric dry electrodes and the skin is relatively large, and the fit between the fabric dry electrodes and the skin is often not tight enough. When testing movements other than sitting postures, such as running and jumping, it is very easy for the measurement of physiological electrical signals to fail due to the vigorous activities of the human body. The area of fabric electrodes is often relatively large. When the size is reduced to a certain extent (such as millimeter level), the flexibility of the fabric electrodes will drop sharply, and it is easy to cause strong discomfort when wearing them.
[0076] Microneedle electrodes are an important physiological electrical electrode developed in recent years. However, in the current process of using microneedle electrodes to monitor human health, the contact impedance between microneedle electrodes and the skin is large, the comfort level is low when worn, and the biocompatibility and air permeability of microneedle electrodes with human skin are poor when worn for a long time, which can easily cause skin allergies and damage.
[0077] Based on this, firstly, Figure 1a The schematic diagram of the structure of the microneedle electrode provided in this application is as follows: Figure 1a As shown, the microneedle electrode 100 comprises:
[0078] A microneedle body 10, wherein the microneedle body 10 comprises a contact portion 11 for contacting the skin, wherein the contact portion 11 is made of a composite silk protein material, wherein the composite silk protein material is formed by a polymer, a metal nanowire and a silk protein through mesoscopic hybridization; and
[0079] A flexible base layer 30 is electrically connected to the microneedle body.
[0080] In the above scheme, the microneedle electrode provided by the present application has a contact portion that contacts the skin using a composite silk protein material including polymers, silk proteins and metal nanowires. This composite silk protein material utilizes the microscopic directional reconstruction of metal nanowires, polymers and silk proteins, and achieves highly uniform conductivity on the surface and inside of the contact portion through the "quantum tunnel effect" of the metal nanowires, and has both biocompatibility and breathability, so that the microneedle electrode has excellent mechanical stability and chemical stability, and has the advantages of resistance to salt spray, sweat, alcohol, soap solution, and cleaning.
[0081] The microneedle electrodes provided in this application can be used to monitor physiological electrical signals for a long time. In the expanding global medical and health industry, microneedle electrodes have the advantages of low contact impedance, high sensitivity, close fit, flexible skin-friendly, stable and durable, and can be worn comfortably for a long time. Specifically, physiological electrical signals mainly include electromyography (EMG), electrocardiography (ECG), electroencephalography (EEG), electrodermal (EDA), electrooculography (EOG), and electrogastric (EGG) signals. It can be understood that physiological electrical electrodes can convert the ion potential generated by electrochemical activity in the body into a current that can be identified and characterized by the measurement system, and play the role of a transducer, which belongs to a kind of sensor. Specifically, the current is conducted by ions in the body, by electrons in the electrodes and wires, and at the contact interface between the electrodes and human skin, the ion current is converted into an electronic current, so that the organism and the measuring instrument system together constitute a current loop. The microneedle electrodes provided in this application are flexible physiological electrical electrodes with the advantages of low contact impedance, close fit, flexible skin-friendly, stable and durable, and can be worn comfortably for a long time.
[0082] In some embodiments, Figure 1aAs shown, the microneedle body 10 also includes a substrate 12, and the contact portion 11 is arranged on at least a portion of the surface of the substrate 12. Specifically, the contact portion 11 is a contact layer with a smooth surface. It can be understood that the smooth contact layer can reduce the foreign body sensation when in contact with the skin, and the wearing comfort can be further improved. In other embodiments, the contact portion 11 can also be a structure of other layers, columns, cones, etc., as long as the contact portion can contact the skin, it is not limited in this application.
[0083] Figure 1b Another structural schematic diagram of the microneedle electrode provided in this application is as follows: Figure 1b As shown, the contact portion is a contact layer 11 with convex points on the surface. It can be understood that these surface convex points can increase the contact stability with the skin and enhance the transmission of myoelectric signals.
[0084] Figure 1c Another structural schematic diagram of the microneedle electrode provided in this application is as follows: Figure 1c As shown, the contact part 11 is a plurality of electrode needles arranged in an array. The electrode needles can be directly connected to the flexible base layer 30 or indirectly connected through the substrate 12.
[0085] The electrode needle can be a pointed cone or needle-shaped structure, which can easily penetrate the stratum corneum of the skin. Compared with some metal-based electrode needle structures, the electrode needle prepared by the composite silk protein material in the present application is not prone to the risk of breaking during use, and the flexible base layer 30 of the microneedle electrode of the present application can fit closely with the skin, which can improve the comfort of long-term wearing.
[0086] In some embodiments, the end of the electrode needle has an arc surface. The present application has rounded the end structure of the electrode needle. Compared with other pointed cones, needle-shaped structures, etc., when the microneedle structure contacts the skin, it is not easy to remain partially in the skin. The microneedle electrode of the present application does not have a needle tip that pierces the skin. The electrode needle will not break after thousands of frictions, and the conductivity is not affected, so it can be used repeatedly.
[0087] Specifically, the electrode needle includes a cylindrical cylindrical portion and a hemispherical end portion. The electrode needle of this structure has both strength and toughness, and has good mechanical stability; and the bending resistance, friction resistance and stretching resistance are significantly enhanced. Compared with the technical solution of coating a conductive layer on the surface of the microneedle, the microneedle electrode of the present application still maintains its morphology intact after bending, friction, and stretching, and the contact impedance with the skin can remain stable. The conductivity will not be significantly weakened when characterizing electrocardiographic and electromyographic signals, and the conductive performance is stable; there is no risk of the conductive layer falling off.
[0088] In order to ensure the repeated use of the electrode needle and its structural stability, the diameter of the electrode needle is 400μm to 600μm; specifically, it can be 400μm, 420μm, 450μm, 470μm, 500μm, 520μm, 550μm, 570μm, 580μm or 600μm, etc., or other values within the above range, which are not limited here. From the perspective of balancing cost and structural strength, the diameter of the electrode needle is preferably 500μm to 550μm.
[0089] In some embodiments, the protruding height of the electrode needle is 700 μm to 900 μm; specifically, it can be 700 μm, 750 μm, 800 μm, 850 μm, 880 μm, 890 μm or 900 μm, etc., or other values within the above range, which are not limited here. Preferably, the protruding height of the electrode needle is 750 μm to 850 μm. Controlling the protruding height of the electrode needle can ensure that the electrode needle of the microneedle electrode can fully and stably contact with human skin.
[0090] In some embodiments, the spacing between two adjacent electrode needles is 800μm to 1200μm, specifically 800μm, 850μm, 900μm, 950μm, 1000μm, 1050μm, 1100μm, 1050μm or 1200μm, etc., or other values within the above range, which are not limited here. It can be understood that the spacing between electrode needles affects the distribution density of electrode needles in the microneedle electrode. Too high density increases the cost, and too low density reduces the effective contact with human skin, thereby affecting the detection accuracy of the electrode. Preferably, the spacing between two adjacent electrode needles is 900μm to 1000μm.
[0091] It should be noted that the protruding height, diameter and spacing of the electrode needles of the microneedle body can also be adjusted according to actual conditions and are not limited here.
[0092] In some embodiments, the microneedle body 10 is made of a composite silk protein material, and the matrix 12 and the contact portion 11 are integrally formed. That is, the matrix 12 and the contact portion 11 are cast and formed by the composite silk protein material, which can simplify the preparation process, improve the overall structural stability of the matrix and the contact portion, and also achieve more uniform conductivity.
[0093] In the present application, the microneedle body 10 is made of a composite silk protein material, and the microneedle body 10 is in direct contact with the skin to collect physiological electrical signals. The microneedle body 10 has uniform overall conductivity from the inside to the outside, which can reduce the contact impedance with the skin. Since the materials of the electrode needle and the base part of the microneedle body can be selected according to actual conditions, the contact impedance between the microneedle body made of different materials and the skin will also fluctuate to a certain extent.
[0094] In other embodiments, the material of the substrate 12 may also be different from that of the contact portion 11 , for example, it may be a polymer, and the polymer is selected from at least one of polyurethane, silica gel, polyacrylamide, and natural polymers.
[0095] In some embodiments, Figure 1c As shown, the base 12 has a receiving cavity 121 , a flexible filling layer 20 is disposed in the receiving cavity 121 , and the flexible base layer 30 seals the receiving cavity 121 of the base 12 ; the contact portion 11 is disposed on a surface of the base 12 away from the receiving cavity 121 .
[0096] It can be understood that filling the flexible filling layer in the receiving cavity of the substrate can reduce the amount of composite silk protein material used and reduce costs. At the same time, the use of a flexible filling material with better softness can improve the wearing comfort of the microneedle electrode after the microneedle electrode is attached to the skin. When the contact portion is a contact layer with convex points on the surface or a contact layer with a smooth surface, the contact layer can be stacked on the surface of the substrate.
[0097] Figure 2a This is a three-dimensional structural effect diagram of the microneedle electrode provided in this application. Figure 2b The three-dimensional decomposition structure effect diagram of the provided microneedle electrode; Figure 2a and Figure 2b As shown, in some embodiments, the surface of the substrate 12 of the microneedle body 10 connected to the electrode needle 11 is circular, and a plurality of electrode needles are arranged in a central annular array along the surface of the substrate.
[0098] In some embodiments, the substrate 12 is a cap-shaped structure, the substrate 12 includes a main body and a brim, the main body is provided with a receiving cavity 121, a flexible filling layer 20 is provided in the receiving cavity 121, and the brim is sealed and connected to the flexible base layer 30.
[0099] Specifically, the main body can be a cylindrical structure with one end open, and the brim is connected to the open end of the main body. The extension width of the brim can be 1 mm to 1.6 mm. The structural design of the brim is conducive to the connection between the microneedle body 10 and the flexible base layer 30, which is convenient for the installation of microneedle electrodes for wearable devices. When under force, the microneedle electrodes can fit tightly to the skin, and can successfully monitor human physiological electrical signals such as electrocardiogram and electromyography signals in motion.
[0100] Specifically, the diameter of the main body can be 5 mm to 6 mm, and the protruding height of the main body can be 1.2 mm to 1.5 mm. The brim part is an annular structure, and the extension width of the brim part is 1.2 mm to 1.5 mm.
[0101] In some embodiments, the material of the microneedle body 10 is a composite silk protein material, and the composite silk protein material is formed by polymers and metal nanowires participating in the reconstruction of the mesostructure of silk protein. The present application uses a composite silk protein material to form the microneedle body 10 in an integrated manner, so that the surface and interior of the electrode needle can achieve highly uniform conductivity. At present, some technical solutions for forming a conductive layer on the surface of the electrode needle will cause the entire microneedle electrode to be scrapped after the conductive layer is worn out, and the use cost is high and cannot be reused. The microneedle body in the present application is formed in an integrated manner using a composite silk protein material. Even if the surface of the electrode needle is partially worn, it can maintain good conductivity and has excellent sweat resistance and corrosion resistance. During long-term use, its conductivity is not affected by long-term contact with sweat and sebum secreted by the skin, so that the microneedle electrode can be used for long-term monitoring of various physiological electrical signals of the human body.
[0102] Furthermore, if Figure 2a and Figure 2b As shown, the flexible filling layer 20 is disposed in the accommodating cavity 121 of the microneedle body 10. The material of the flexible filling layer 20 may be a polymer, and the polymer is selected from at least one of polyurethane, silica gel, polyacrylamide, and natural polymers. In actual situations, the flexible filling layer can be prepared by selecting polymers with different elastic moduli, and the overall hardness and softness of the microneedle electrode can be adjusted by adjusting the height and components of the flexible filling layer, thereby improving the comfort of the microneedle electrode when used on human skin for a long time, such as reducing the pressure and tingling sensation.
[0103] The flexible substrate layer 30 is electrically connected to the microneedle body 10, and the flexible substrate layer 30 closes the accommodating cavity 121 of the microneedle body 10. The flexible substrate layer 30 is used to connect with a wearable device. In the present application, the material of the flexible substrate layer 30 is a composite silk protein material, that is, the material of the microneedle body 10 and the flexible substrate layer 30 is the same, and has considerable conductivity. The microneedle body 10 can transmit the collected physiological signals to the flexible substrate layer, and then the flexible substrate layer 30 transmits them to the monitoring electronic device.
[0104] It can be understood that the flexible filling layer 20 and the microneedle body 10 are encapsulated using the flexible base layer 30, which not only ensures the structural stability of the microneedle electrode as a whole, but also enables the microneedle electrode as a whole to be flexibly and firmly used with different wearable devices, greatly expanding the application scenarios of the microneedle electrode.
[0105] Figure 3 Schematic diagram of the actual application scenario of the microneedle electrode provided in this application, such as Figure 3 As shown, when the prepared flexible microneedle electrode is used in combination with medical tape, a universal standard electrode similar to the commercial AgCl / AgCl wet electrode can be made and applied to the monitoring of human physiological electrical signals.
[0106] In some specific embodiments, the preparation of the microneedle electrode may include the following steps:
[0107] Step 01, preparing a silk fibroin solution; wherein the silk fibroin can be selected from mulberry silkworm cocoons and / or tussah silkworm cocoons, etc.
[0108] Step 02, preparing a polymer solution;
[0109] Step 03, preparing a metal nanowire solution;
[0110] Step 04, the three solutions are mixed evenly according to a certain proportion, and an appropriate amount of a cross-linking agent is added to obtain a mixed solution;
[0111] Step 05, evenly pouring the mixed solution into the pre-treated microneedle body template, and obtaining the microneedle body after curing.
[0112] Wherein, the microneedle body template includes but is not limited to a metal microneedle body template, a silicon microneedle body template, a ceramic microneedle body template or a polymer microneedle body template. Further, the metal microneedle body template includes but is not limited to an aluminum template, a stainless steel template and a titanium template. Further, the contact portion in the microneedle body template may be a contact layer on a smooth surface, a contact layer on a convex surface or an electrode needle. The needle shape of the electrode needle includes but is not limited to a cone, a pyramid, and a cylindrical sphere.
[0113] Step 06, uniformly pouring the polymer solution into the receiving cavity of the microneedle body, using the receiving cavity as a template, and preparing a flexible filling layer by solidifying the polymer solution;
[0114] Step 07, using the mixed solution prepared in step 04 to prepare a flexible base layer; and then using the flexible base layer to encapsulate the flexible filling layer and the microneedle body layer.
[0115] In the above scheme, the nucleation path and dynamics of silk protein molecules in the self-assembly process are regulated by polymers and metal nanowires, and the mesoscopic structure of the composite silk protein material is reconstructed in a directional manner to achieve performance improvement and mesoscopic functionalization. Compared with the method of simply mixing silk protein molecules with other additives and then casting them into shape, the mesoscopic multi-level structure of the composite silk protein material has undergone significant changes through the reconstruction of the mesoscopic structure of silk protein. In the composite silk protein material, due to the mesoscopic template effect of the polymer, a large number of silk protein molecules are gathered around it, and a large number of metal nanowires are extended and grown outward, thereby constructing the mesoscopic multi-level structure of the composite silk protein material, improving the mechanical properties and chemical stability of the composite silk protein material, so that the microneedle electrode prepared from the composite silk protein material has the advantages of low contact impedance, high sensitivity, tight fit, flexible skin-friendly, stable and durable, and can be worn comfortably for a long time.
[0116] In some embodiments, the silk fibroin solution is a silk fibroin solution obtained by degumming, dissolving and dialyzing natural silkworm cocoons; the mass fraction of the silk fibroin solution is 2wt% to 8wt%, specifically 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 7.5wt%, 7.8wt% or 8wt%, etc., which is not limited here.
[0117] In some embodiments, the polymer in the high molecular polymer solution can be polyurethane, polyacrylamide, polyvinyl alcohol, etc., which can interact with silk fibroin molecules. Preferably, the polymer is waterborne polyurethane.
[0118] In some embodiments, the metal nanowire solution can be selected from a metal-based nanowire aqueous dispersion, such as a silver nanowire aqueous dispersion, and the metal nanowire is selected from at least one of gold nanowires, silver nanowires, copper nanowires, and stainless steel nanowires. These metal nanowires have good electrical conductivity, and can still exhibit good overall electrical conductivity when the density of the metal nanowires is low. Preferably, the metal nanowires are silver nanowires.
[0119] In some embodiments, the flexible filling layer may be formed by solidifying a high molecular polymer, or may be formed by solidifying a composite silk protein material of a high molecular polymer and silk protein.
[0120] In some embodiments, silk cocoon silk can be degummed and subjected to a series of chemical treatments to obtain a silk protein solution, and polymers and metal nanowires are added to the silk protein solution to induce the silk protein molecules to undergo heterogeneous nucleation and self-assembly with the polymer molecules as mesoscopic templates to achieve directional reconstruction, thereby achieving directional regulation of the self-assembly process of the silk protein molecules in the silk protein solution, so that the microneedle body has good mechanical properties, chemical stability and excellent electrical properties.
[0121] In some embodiments, the molecular weight of silk protein is 25 kDa to 130 kDa, and specifically can be 25 kDa, 50 kDa, 75 kDa, 90 kDa, 100 kDa, 110 kDa, 125 kDa or 130 kDa, etc., which is not limited here.
[0122] In some embodiments, the metal nanowires include at least one of gold nanowires, silver nanowires, copper nanowires and stainless steel nanowires. These metal nanowires have good electrical conductivity. In the composite silk protein material, the metal nanowires can still show good overall electrical conductivity when the density is low. Preferably, the metal nanowires are silver nanowires.
[0123] In some embodiments, the aspect ratio of the metal nanowire is <1000, and specifically can be 999, 950, 900, 850, 800, 750, 700, 650, 600, 500, 400, 300, 200, etc., which are not limited here. In order to reduce the cost of materials, the present application can select metal nanowires with an aspect ratio of less than 600 to prepare composite silk protein materials. Since the composite silk protein material provided by the present application does not rely solely on the physical contact between the metal nanowires to achieve conductivity, the aspect ratio of the metal nanowires is relatively low, and the purpose of overall conductivity can be achieved when the concentration of the metal nanowires is relatively low. The metal nanowires with a relatively small aspect ratio can reduce the cost of raw materials and can significantly reduce the preparation cost of microneedle electrodes.
[0124] In some embodiments, the diameter of the metal nanowire is 60 nm to 100 nm, specifically 60 nm, 70 nm, 80 nm, 90 nm or 100 nm, etc., and may also be other values within the above range.
[0125] In some embodiments, the length of the metal nanowire is 5 μm to 60 μm, specifically 5 μm, 10 μm, 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm, 50 μm or 60 μm, etc., or other values within the above range, which are not limited here. When the length of the metal nanowire is short, it is necessary to increase the distribution density of the metal nanowire in the composite silk protein material. When the length of the metal nanowire is long, the distribution density of the metal nanowire in the composite silk protein material can be reduced, but the longer the metal nanowire, the higher the production cost. Considering the overall conductivity and cost, the length of the metal nanowire is preferably 20 μm to 50 μm.
[0126] In some embodiments, the mass content of the metal nanowires in the composite silk protein material is 2% to 10%, specifically 2%, 3%, 3.5%, 4%, 5%, 6%, 7%, 8%, 9.5% or 10%, etc., which is not limited here.
[0127] Figure 4The conductivity of the microneedle electrode provided in the present application varies with the amount of metal nanowires added. Taking silver nanowires as an example, the conductivity of the composite silk protein material increases with the increase in the amount of silver nanowires added. Without affecting the conductivity of the composite silk protein material, from a cost perspective, the mass content of the metal nanowires in the composite silk protein material is 3% to 6.8%. In the present application, adding metal nanowires with a relatively low content and a relatively low aspect ratio to the composite silk protein material can give the microneedle electrode excellent and stable conductivity. This is because the metal nanowires participate in the directional reconstruction of the composite material due to the stable mesoscopic electronic structure within the composite silk protein material. Compared with coating a conductive layer on the surface of the microneedle electrode, this composite structure is more stable and the conductivity is more uniform.
[0128] Figure 5 Schematic diagram of the quantum tunneling mechanism of metal nanowires in the microneedle electrode provided in this application, such as Figure 5 As shown in the figure, since the metal nanowires are used as mesoscopic nucleation templates for silk protein molecules, these metal nanowires themselves are retained in the mesoscopic multi-level network structure of the composite silk protein material of the microneedle electrode, so the structure is very stable; more importantly, due to the low potential of the metal nanowires, taking the silver nanowires as an example, a potential well with a low potential is generated around them, that is, a mesoscopic hole is formed; under the action of the electric field, the positively charged silver ions will migrate between adjacent mesoscopic holes, and even migrate between holes formed by metal nanowires that are not in direct contact, that is, through this quantum tunneling effect (QTE), these metal nanowires that are not in physical contact are connected, which actually promotes the overall conductivity of the microneedle electrode. This tunneling effect of metal nanowires ensures that even with a low metal nanowire mass content and a small aspect ratio, excellent conductivity can still be obtained, which not only reduces the manufacturing cost of the microneedle, but also reduces the problem of high overall hardness of the composite material caused by a high content of metal nanowires, and significantly optimizes the pressure and discomfort when the electrode contacts the human body.
[0129] In some embodiments, the polymer in the composite silk protein material is selected from at least one of polyurethane, polyacrylamide, polyvinyl alcohol, and cellulose.
[0130] In some embodiments, the mass content of the polymer in the composite silk protein material is 30% to 40%. Specifically, it can be 30%, 31%, 32%, 33%, 34%, 35%, 36%, 37%, 38%, 39% or 40%, etc., which is not limited here. It can be understood that by regulating the proportion of polymer molecules in the mixed solution, the directional reconstruction of the structure (especially the mesostructure) of the composite silk protein material can be effectively achieved.
[0131] In some embodiments, the polymer in the composite silk protein material is a polyurethane having a hard segment and a soft segment, in which the hard segment and the soft segment are arranged alternately. Among them, the hard segment of the polymer can serve as a template for inducing the self-assembly of silk protein molecules, and the soft segment can provide additional flexibility to the composite silk protein material. Specifically, the hard segment of the polyurethane contains a strong polar group, so that the hard segment has extremely strong rigidity, and the strong polar group is selected from amino, formate, amide, cyanate, etc.; the hard segment of the polyurethane contains a strong polar group. The soft segment of the polyurethane can be polyether polyols, polyesters, etc., and the soft segment can also be encapsulated to a certain extent by methyl, so that the composite silk protein material achieves a balance between strength and elasticity.
[0132] For example, the hard segment of the polyurethane may be polyisocyanate, and its monomer may be at least one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, naphthalene 1.5-diisocyanate, isophorone diisocyanate, m-dimethylene diisocyanate, p-phenylene diisocyanate, 3,3.-dimethyl-4,4.-biphenyl diisocyanate, 4,4'-dicyclohexylmethane diisocyanate, hydrogenated toluene diisocyanate, and trimethylhexamethylene diisocyanate. The soft segment may be polyethylene glycol.
[0133] Specifically, the molar ratio of the hard segment to the soft segment is greater than 3: 1. The molar ratio of the hard segment to the soft segment can be 3.1: 1, 3.5: 1, 4: 1, 5: 1, 6: 1, 7: 1, 8: 1, 9: 1 or 10: 1, etc. The molar ratio of the hard segment is controlled within the above range, which is beneficial to improve the mechanical strength of the composite silk protein material.
[0134] In the present application, the composite silk protein material is formed by the composite of polymer, metal nanowire and silk protein through mesoscopic hybridization. Figure 6a A comparison chart of the β-folding content in the composite silk protein material and silk protein provided in the present application; Figure 6b A comparison chart of the content of β crystallites in the composite silk protein material and silk protein provided in this application; Figure 6a and Figure 6b As shown, the β-folding content in the composite silk protein material is 44% to 49%, and the β-crystal content is 35% to 40%. In pure silk protein material, the β-folding content is less than 38%, and the β-crystal content is less than 30%. It can be seen that after the mesoscopic structure of silk protein is reconstructed by polymer and metal nanowires, it can have a higher β-folding content and β-crystal content. The β-crystal content can be used to characterize the crystallinity of the material. The improvement of crystallinity can improve the mechanical properties and corrosion resistance of the material.
[0135] After X-ray diffraction testing, the size of β crystallites in the composite silk protein material meets the following requirements: La<2.5nm, Lb<4.0nm, Lc<10.1nm.
[0136] The present application also provides a wearable device, which includes a microneedle electrode, and is mainly used for long-term measurement of various physiological electrical signals of the human body, including electrocardiogram signals and electromyogram signals. According to the actual application scenario, the flexible microneedle electrode of the present application is bonded to the medical tape and then affixed to the corresponding measurement part of the human body. Exemplarily, when testing the electrocardiogram signal, a group of microneedle electrode pairs are respectively affixed to the wrists of both hands. When testing the electromyogram signal, a pair of microneedle electrodes are respectively affixed to the two ends of the corresponding muscle fibers. The measured physiological electrical signal is transmitted by leading out a wire from the back of the microneedle electrode, and then the signal is transmitted to the wearable device for analysis by wireless or wired methods. The physiological electrical signals of the microneedle electrode when testing different movement postures of the human body (such as sitting, standing, lying, walking, jogging, etc.) are as follows. Figure 3 As shown, you only need to add medical tape around the electrode and let it fit tightly to the skin.
[0137] The above are only preferred embodiments of the present application and are not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the scope of protection of the present application.
[0138] The present application is further described below through specific embodiments.
[0139] Example 1
[0140] (1) preparing a regenerated silk fibroin solution, a polymer solution and a metal nanowire solution;
[0141] Selecting mulberry silkworm cocoons and tussah silkworm cocoons as silk fibroin to prepare a silk fibroin solution with a mass fraction of 5 wt%;
[0142] preparing an aqueous polyurethane solution, wherein the mass fraction of the aqueous polyurethane is 35%;
[0143] Selecting a silver nanowire aqueous dispersion as the metal nanowire solution, the mass content of the silver nanowires is 20 mg / ml;
[0144] (2) The silk fibroin solution, the polymer solution and the metal nanowire solution are mixed and dispersed to obtain a mixed solution, wherein the volume ratio of the silk fibroin solution, the aqueous polyurethane solution and the silver nanowire solution is 2:3:7, and the mixed solution also includes a cross-linking agent aziridine accounting for 2% of the volume fraction of the mixed solution.
[0145] (3) Preparation of microneedle body
[0146] The mixed solution was poured into the microneedle body silicone template, and demoulded after curing to obtain the microneedle body, wherein the protrusion height of the electrode needle was 750 μm, the diameter of the electrode needle was 500 μm, and the distance between adjacent electrode needles was 1000 μm.
[0147] (4) Preparation of flexible filling layer
[0148] A mixed solution of silk fibroin solution and high molecular polymer solution is injected into the accommodating cavity of the microneedle body, and the accommodating cavity is used as a template, and a flexible filling layer is formed after solidification.
[0149] (5) Preparation of flexible substrate
[0150] The mixed solution is injected into the base template, and the flexible base layer is obtained by curing and demoulding. The flexible base layer and the microneedle body layer are bonded and packaged with conductive silver glue. The bonded microneedle electrodes are placed in a 50°C oven for drying.
[0151] Example 2
[0152] The difference from Example 1 is:
[0153] (2) The silk fibroin solution, the aqueous polyurethane solution and the copper nanowire solution are mixed and dispersed to obtain a mixed solution.
[0154] Example 3
[0155] The difference from Example 1 is:
[0156] (2) The silk fibroin solution, the polymer solution and the metal nanowire solution are mixed and dispersed to obtain a mixed solution, wherein the volume ratio of the silk fibroin solution: the aqueous polyurethane solution: the silver nanowire solution is 3:4:5.
[0157] Example 4
[0158] The difference from Example 1 is:
[0159] In the prepared microneedle body, the protrusion height of the electrode needle is 600 μm, the diameter of the electrode needle is 500 μm, and the distance between adjacent electrode needles is 800 μm.
[0160] Performance Test:
[0161] 1) Test of contact impedance between microneedle electrode and skin:
[0162] The microneedle electrode prepared in the above-mentioned Example 1 was applied to the measurement of electromyographic signals.
[0163] Figure 7a Schematic diagram of the impedance test results of the microneedle electrode prepared in Example 1 of the present application, as shown in Figure 7aAs shown, in the frequency range of 20-500 Hz, when the microneedle electrode prepared in Example 1 is compared with a commercial Ag / AgCl wet electrode of the same area, the contact impedance between the microneedle electrode in Example 1 and the skin is basically the same as the contact impedance between the commercial wet electrode and the skin. The microneedle electrode of the present application has lower impedance in the low-frequency range and better performance.
[0164] 2) Test of signal-to-noise ratio between microneedle electrodes and skin:
[0165] Figure 7b Schematic diagram of the signal-to-noise ratio test results of the microneedle electrode prepared in the embodiment of the present application, as shown in Figure 7b As shown, under the same test conditions such as electrode size, test object, sitting posture, etc., the microneedle electrode prepared in Example 1 is used to measure the corresponding electromyographic signals at rest and during finger-snapping movements, and the signal-to-noise ratio is calculated. Finally, it is compared with the commercial Ag / AgCl wet electrode. The results confirm that after performing an FFT operation on the motion signal from the time domain to the frequency domain, within the frequency range of 20-500 Hz, the signal-to-noise ratio of the finger-snapping signal of the microneedle electrode of Example 1 is about 20 decibels, and the signal-to-noise ratio of the microneedle electrode of Example 1 is equal to that of the commercial wet electrode.
[0166] 3) Test of chemical stability of microneedle electrodes:
[0167] 3.1 Sweat corrosion resistance:
[0168] The microneedle electrodes were immersed in artificially prepared sweat and placed in a constant temperature and humidity chamber at 37°C and 60 RH% for 7 days. After being taken out, they were washed and dried, and the morphology of the microneedle electrodes before and after immersion was compared. The contact impedance between the microneedle electrodes and the skin before and after immersion was tested and the contact impedance was compared.
[0169] Figure 8a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in sweat. Figure 8b This is a comparison chart of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in sweat. Figure 8a to Figure 8b As shown, the appearance of the microneedle electrode prepared in Example 1 did not change after being immersed in human sweat, and the contact impedance and signal-to-noise ratio of the microneedle electrode did not change significantly, and its electrical performance was stable.
[0170] 3.2 Resistance to concentrated salt water corrosion:
[0171] The microneedle electrodes were immersed in a 6% artificially prepared concentrated saline solution and placed in a constant temperature and humidity chamber at 37°C and 60RH% for 7 days. After being taken out, they were washed and dried, and the morphology of the microneedle electrodes before and after immersion was compared. The contact impedance between the microneedle electrodes and the skin before and after immersion was tested and the contact impedance was compared.
[0172] Figure 9a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in concentrated salt water. Figure 9b This is a comparison diagram of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in concentrated salt water, as shown in FIG. Figure 9a to Figure 9b As shown, the appearance of the microneedle electrode prepared in Example 1 did not change after being immersed in concentrated salt water, the contact impedance of the microneedle electrode did not change significantly, and its electrical performance was stable.
[0173] 3.3 Alcohol resistance:
[0174] The microneedle electrode was immersed in 75% alcohol and placed in a constant temperature and humidity chamber at 37°C and 60RH% for 7 days. After being taken out, it was washed and dried, and the morphology of the microneedle electrode before and after immersion was compared, and the contact impedance between the microneedle electrode and the skin before and after immersion was tested, and the contact impedance was compared. After the microneedle electrode prepared in Example 1 was treated with alcohol immersion, the appearance did not change, and the contact impedance of the microneedle electrode did not change significantly, and its electrical performance was stable.
[0175] 3.4 Grease resistance:
[0176] The microneedle electrodes were immersed in vegetable oil and placed in a constant temperature and humidity chamber at 37°C and 60 RH% for 7 days. After being taken out, they were washed and dried, and the morphology of the microneedle electrodes before and after immersion was compared. The contact impedance between the microneedle electrodes and the skin before and after immersion was tested and compared.
[0177] Fig.10a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in vegetable oil. Fig.10b This is a comparison chart of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after being immersed in vegetable oil. Figure 10a to Figure 10b As shown, the appearance of the microneedle electrode prepared in Example 1 did not change after being immersed in vegetable oil, and the contact impedance of the microneedle electrode did not change significantly, and its electrical performance was stable.
[0178] 3.4 Anti-fouling ability:
[0179] The microneedle electrodes were worn continuously for 5 days without being cleaned. The contact impedance between the microneedle electrodes and the skin was tested before and after wearing, and the contact impedance was compared.
[0180] Fig.11 This is a comparison chart of the microneedle electrode prepared in Example 1 of the present application before and after wearing for 5 days. Fig.11 As shown, the contact impedance of the microneedle electrode prepared in Example 1 does not change significantly before and after long-term wearing without cleaning, and its electrical performance is stable.
[0181] 3.4 High and low temperature resistance:
[0182] The microneedle electrodes were placed in -20℃ and 80℃ environments for 24 hours continuously, and the contact impedance between the microneedle electrodes and the skin was tested before and after the test, and the contact impedance was compared.
[0183] Fig.12 This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after low-temperature storage, as shown in FIG. Fig.12 As shown, the contact impedance of the microneedle electrode prepared in Example 1 did not change significantly before and after low-temperature storage, and its electrical performance was stable.
[0184] 4) Testing of mechanical properties of microneedle electrodes:
[0185] 4.1 Tensile resistance test
[0186] The microneedle electrode was stretched by 5% and stretched continuously for 1000 times to test its morphology and electrical properties.
[0187] Fig.13a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after the stretching test. Fig.13b The figure is a comparison of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after the tensile test. Figure 13a to Figure 13b As shown, after the microneedle electrode prepared in Example 1 has been subjected to a thousand times of tensile test, the appearance of the microneedle electrode has not changed, and the contact impedance of the microneedle electrode has not changed significantly, and its electrical performance is stable.
[0188] 4.2 Bending resistance test
[0189] The microneedle electrode was bent continuously 1000 times to test its morphology and electrical properties.
[0190] Fig.14a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after the bending test. Fig.14b The figure is a comparison of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after the bending test. Figure 14a to Figure 14b As shown, after the microneedle electrode prepared in Example 1 has been subjected to a thousand times of bending test, the appearance of the microneedle electrode has not changed, and the contact impedance of the microneedle electrode has not changed significantly, and its electrical performance is stable.
[0191] 4.3 Wear resistance test
[0192] The microneedle electrode was rubbed back and forth 1000 times with 40g depilated pig skin to test its morphology and electrical properties.
[0193] Fig.15a This is a comparison diagram of the microneedle electrode prepared in Example 1 of the present application before and after the wear resistance test. Fig.15bThe following is a comparison chart of the contact impedance of the microneedle electrode prepared in Example 1 of the present application before and after the wear resistance test. Figure 15a to Figure 15b As shown, after the microneedle electrode prepared in Example 1 has been subjected to a thousand times of wear resistance test, the appearance of the microneedle electrode has not changed, and the contact impedance of the microneedle electrode has not changed significantly, and its electrical performance is stable.
[0194] In summary, the microneedle electrode of the present application adopts a composite silk protein material including polymers, silk proteins and metal nanowires. This composite silk protein material uses metal nanowires and polymers to carry out directionally reconstructed mesoscopic structures of silk proteins. Through the "quantum tunneling effect" of the metal nanowires, highly uniform conductivity is achieved on the surface and inside of the electrode needle, and it has both biocompatibility and air permeability, so that the microneedle electrode has excellent mechanical stability and chemical stability, and has the advantages of resistance to salt spray, sweat, alcohol, soap solution, and cleaning; secondly, filling a flexible filling layer in the accommodating cavity of the substrate can reduce the use of the composite silk protein material and reduce costs. At the same time, the use of a flexible filling material with better softness can improve the wearing comfort of the microneedle electrode after the microneedle electrode is fitted to the skin.
Claims
1. A microneedle electrode, characterized in that: The microneedle electrode comprises: A microneedle body, wherein the microneedle body comprises a contact portion for contacting the skin, wherein the contact portion is made of a composite silk protein material, wherein the composite silk protein material is formed by a polymer, a metal nanowire and a silk protein through mesoscopic hybridization; and A flexible base layer is electrically connected to the microneedle body.
2. The microneedle electrode according to claim 1, characterized in that: It meets at least one of the following characteristics: a. The contact portion is a plurality of electrode needles arranged in an array; b. The contact portion is a plurality of electrode needles arranged in an array, and the end of the electrode needle has a curved surface; c. The contact portion is a plurality of electrode needles arranged in an array, and the electrode needles include a cylindrical body and a hemispherical end; d. The contact portion is a contact layer having convex points on the surface; e. The contact portion is a contact layer with a smooth surface.
3. The microneedle electrode according to claim 2, characterized in that: The microneedle body further comprises a substrate, and the contact portion is arranged on at least a portion of the surface of the substrate.
4. The microneedle electrode according to claim 3, characterized in that: The microneedle body is made of composite silk protein material, and the base and the contact part are integrally formed.
5. The microneedle electrode according to claim 3, characterized in that: The base has a receiving cavity, a flexible filling layer is arranged in the receiving cavity, and the flexible base layer seals the receiving cavity of the base; the contact part is arranged on a surface of the base away from the receiving cavity.
6. The microneedle electrode according to claim 3, characterized in that: The base body is a cap-shaped structure, comprising a main body and a brim portion, the main body portion is provided with a receiving cavity, a flexible filling layer is provided in the receiving cavity, and the brim portion is sealed and connected to the flexible base layer.
7. The microneedle electrode according to any one of claims 1 to 6, characterized in that: It meets at least one of the following characteristics: a. The metal nanowires include at least one of gold nanowires, silver nanowires, copper nanowires and stainless steel nanowires; b. The aspect ratio of the metal nanowire is <1000; c. The length of the metal nanowire is 5 μm to 60 μm; d. The silk protein is selected from at least one of mulberry silk, tussah silk and castor silk; e. The molecular weight of the silk protein is 25 kDa to 130 kDa; f. The mass content of the metal nanowires in the composite silk protein material is 2% to 10%.
8. The microneedle electrode according to any one of claims 1 to 6, characterized in that: The β-folding content of the composite silk protein material is 44% to 49%, and the β-crystal content is 35% to 40%; and / or the size of the β-crystals in the composite silk protein material satisfies: La<2.5nm, Lb<4.0nm, Lc<10.1nm.
9. The microneedle electrode according to any one of claims 1 to 6, characterized in that: The polymer in the composite silk protein material is selected from at least one of polyurethane, polyacrylamide, polyvinyl alcohol and cellulose.
10. The microneedle electrode according to any one of claims 1 to 6, characterized in that: The polymer in the composite silk protein material is a polyurethane having a hard segment and a soft segment, and the mass ratio of the hard segment to the soft segment is greater than 3:
1.
11. The microneedle electrode according to claim 10, characterized in that: The hard segment is polyisocyanate, and the soft segment is polyethylene glycol.
12. The microneedle electrode according to claim 4, characterized in that: The material of the flexible base layer is the same as that of the microneedle body.
13. The microneedle electrode according to claim 5 or 6, characterized in that: The material of the flexible filling layer is a polymer, and the polymer is selected from at least one of polyurethane, silica gel, polyacrylamide, and natural polymers.
14. The microneedle electrode according to claim 1, characterized in that: The contact portion is a plurality of electrode needles arranged in an array, which meets at least one of the following characteristics: a. The diameter of the electrode needle is 400 μm to 600 μm; b. The protruding height of the electrode needle is 700 μm to 900 μm; c. The distance between two adjacent electrode needles is 900 μm to 1000 μm.
15. A wearable device, characterized in that: The wearable device comprises the microneedle electrode according to any one of claims 1 to 14.
16. An electronic device, characterized in that: The electronic device comprises the microneedle electrode according to any one of claims 1 to 14.
Citation Information
Patent Citations
Silk microneedle electrode and preparation method thereof
CN109171699A
Adjustable protein-based flexible strain sensor and preparation method and application thereof
CN109737861A
Silver nanothread / silk fibroin composite fiber and preparation method thereof
CN110230113A
Wearable device
CN114052738A
Flexible coated microneedle array electrode for tactile stimulation, preparation method and application
CN115770343A